Proceedings of the 2018 CHI Conference on Human Factors in Computing Systems 2018
DOI: 10.1145/3173574.3174208
|View full text |Cite
|
Sign up to set email alerts
|

D-Swime

Abstract: Smartwatches enable rapid access to information anytime and anywhere. However, current smartwatch content navigation techniques, for panning and zooming, were directly adopted from those used on smartphones. These techniques are cumbersome when performed on small smartwatch screens and have not been evaluated for their support in mobility and encumbrance contexts (when the user's hands are busy). We studied the effect of mobility and encumbrance on common content navigation techniques and found a significant d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Beats [60] explores the design space of 'beating gestures' which are repeated sequential taps made by the index and middle finger of one hand. The design space of smartwatch gestures in the context of mobility and encumbrance has been vividly explored in D-SWIME [77]. With GestureWrist and GesturePad [67], Rekimoto proposed gestural input for on-body wearables.…”
Section: On-body and On-device Wearable Gesturesmentioning
confidence: 99%
“…Beats [60] explores the design space of 'beating gestures' which are repeated sequential taps made by the index and middle finger of one hand. The design space of smartwatch gestures in the context of mobility and encumbrance has been vividly explored in D-SWIME [77]. With GestureWrist and GesturePad [67], Rekimoto proposed gestural input for on-body wearables.…”
Section: On-body and On-device Wearable Gesturesmentioning
confidence: 99%
“…In terms of interaction in different settings, Mo et al [91] investigated the use of smartwatches in mobile contexts like walking and running and found that while walking and operating the smartwatch was similar to sitting, running impacted overall use. In addition to contexts like walking and running, Singh et al [125] explored interaction techniques in cases when only one hand is available compared to both hands for panning and zooming gestures.…”
Section: Smartwatchesmentioning
confidence: 99%
“…This task is important for applications such as instant messages and information editing on AR glasses. In addition to input efficiency, the portability of AR glasses requires an input method to adapt to a wide range of environments and user states, including indoor/outdoor scenes and moving/stationary postures in daily life [62] (as illustrated in Fig. 1).…”
Section: Introductionmentioning
confidence: 99%